ChemInform Abstract: Copper‐Manganese Spinel Oxide Catalyzed Synthesis of Amides and Azobenzenes via Aminyl Radical Cations. Issue 27 (16th June 2016) - Sultan, Shaista; Kumar, Manjeet; Devari, Shekaraiah; Mukherjee, Debaraj; Shah, Bhahwal Ali
Abstract: Amides are prepared by aminolysis of esters via the radical pathway.